THE EFFECTIVENESS OF PARENTING MANAGEMENT TO IMPROVE PARENTS EMPOWERMENT (Case Study of Children's Play Group in Bani Shaleh Bandung) - Nandang Rukanda (IKIP Siliwangi Bandung, 2018)
This study aims to describe the process of implementing parenting programs for learners’ parents in Bani Shaleh Playing Group and application of learning outcomes. The research method used is descriptive qualitative, with the main data collection technique is done through observation and interview, while documentation study is used to strengthen research depth. Subjects were conducted to one of Baya Shaleh Play Group heads, 2 educators, and 5 respondents who were parents of students. The results showed that the process of organizing parenting was successfully implemented by the respondents who showed the ability to establish children when they play. Parents did not intervene in their children’s activities but tend to act as observers and facilitators of their activities. Recommendations are formulated for each child play group to develop parenting activities on a regular basis, while parents should actively participate in this program and all parties need to provide full support not only in the form of attention but also in the form of financial support.